Novel Technologies for Assessing Dietary Intake: Evaluating the Usability of a Mobile Telephone Food Record Among Adults and Adolescents - Daugherty, B.; Schap, T.; Ettienne-Gittens, R.; Zhu, F.; Bosch, M.; Delp, E.; Ebert, D.; Kerr, Deborah; Boushey, C. (Journal of Medical Internet Research, 2012)
The development of a mobile telephone food record has the potential to ameliorate much of the burden associated with current methods of dietary assessment. When using the mobile telephone food record, respondents capture an image of their foods and beverages before and after eating. Methods of image analysis and volume estimation allow for automatic identification and volume estimation of foods. To obtain a suitable image, all foods and beverages and a fiducial marker must be included in the image.